A Survey of Antenna Miniaturization Technology Based on the New Mechanism of Acoustic Excitation - Li, Wanqing; Li, Du; Zhou, Kaixiang; Fu, Qixiang; Yuan, Xuelin; Zhu, Xiangwei (IEEE transactions on antennas and propagation, 2023)
Antenna miniaturization technologies have always been the focus of antenna research. In recent years, mechanical antennas whose size does not depend on the electromagnetic (EM) wavelength have attracted researchers' attention. Acoustically excited antennas (AEAs), as a kind of mechanical antenna, can achieve reciprocal transmission and reception. AEAs utilize internal charge and magnetization oscillations of piezoelectric materials and magnetoelectric (ME) composite materials, respectively, to radiate EM waves, which enables the size of the antenna to be related to the wavelength of the acoustic wave, reducing the size of the antenna by 4-5 orders of magnitude over conventional antennas. Additionally, it is expected to achieve breakthrough application changes in the fields of mobile low-frequency antennas, portable shortwave antennas, and chip-based microwave antennas. In this article, the theory of AEAs is summarized and different modeling and measurement studies of AEAs are described in detail. Finally, the challenges of AEAs research are elaborated and future research on AEAs is prospected.